The Labor Market Returns to 'First in Family' University Graduates - Anna Adamecz-Völgyi; Morag Henderson; Nikki Shure (Institute of Labor Economics (IZA), 2020)
We exploit linked survey-administrative data from England to examine how first in family (FiF) graduates (those whose parents do not have university degrees) fare on the labor market. We find that among graduate women, FiF graduates earn 8.3% less on average than graduate women whose parents have a university degree. For men, we find no such difference. A decomposition of the difference between FiF and non-FiF graduate women reveals that prior academic attainment, whether they attended an 'elite' institution, and whether they needed their degree for their job fully explains this gap. We also estimate returns to graduation for potential FiF and non-FiF young people. We find that although the wage returns to graduation are higher among FiF women compared to women who match their parents with a degree, the negative effects of coming from a lower educated family are so large that they counteract the high returns of graduation.
Keywords: I24; I26; J24; 330; socioeconomic gaps; intergenerational educational mobility; higher education; entropy balancing; labor market returns; gender economics